Salivary Proteome Insights: Evaluation of Saliva Preparation Methods in Mucopolysaccharidoses Research - Maria-Andreea Soporan; Ioana-Ecaterina Pralea; Maria Iacobescu; Radu Cristian Moldovan; Camelia Alkhzouz; Diana Miclea; Cristina-Adela Iuga (Biomedicines)
Background: This research aimed to compare the traditional in-solution digestion (inSol) and solid-phase-enhanced sample preparation (SP3) methods for salivary proteomics, with a focus on identifying mucopolysaccharidosis (MPS)-relevant proteins. Methods: Saliva samples were processed under multiple analytical conditions, including two precipitation methods (methanol or incubation with trichloroacetic acid), paired with either Rapigest or 8M urea/2M thiourea (UT) solubilization buffers. Additionally, the SP3 method was directly applied to raw saliva without pre-processing. Proteome coverage, reproducibility, digestion efficiency, and gene function were assessed. Results: The inSol method consistently provided superior proteome coverage, with trichloroacetic acid precipitation and Rapigest buffer yielding 74 MPS-relevant proteins, compared to 40 with SP3 MeOH UT. Both methods showed high digestion efficiency, particularly with Rapigest buffer, achieving over 80% full cleavage across conditions. Functional analysis revealed broad similarities, with protocol-specific impacts on protein classes and cellular components. Conclusions: This study is the first to compare SP3 and in-solution digestion for salivary proteomics, emphasizing the importance of method selection to address matrix-specific challenges. The results highlight the robustness of inSol for comprehensive proteome profiling and SP3′s potential for streamlined clinical workflows, offering valuable insights into optimizing salivary proteomics for biomarker discovery in MPS and other diseases.